Integrating PBL and flipped classroom to enhance students' argumentation and self-directed learning - Ivatul Laily Kurniawati; Punaji Setyosari; I Wayan Dasna; Henry Praherdhiono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The era of Industrial Revolution 4.0 has triggered an explosion of digitalization in all fields, especially information. This era of Industrial Revolution 4.0 has led to a shift in learning from face-to-face learning in the classroom to online learning. This study will determine students' argumentation skills and self-directed learning (SDL) in students who participate in learning that integrates problem-based learning with the flipped classroom (PBL-FC) and compare them with those who do not. The study was conducted in 2020 on students in two classes of second-grade high school taught by the same teacher in Maluku Province. The control and experimental classes were determined randomly before the study was conducted. The study was conducted for approximately eight weeks. Data were collected using an argumentation skill test and a self-study skill questionnaire. The quantitative data obtained were analyzed using ANOVA. The result is Integration of PBL and FC improves students' skills and helps them see the relationship between concepts as they learn facts and skills by actively working on knowledge rather than passively receiving it.